Pemidanaan Terhadap Anak Pelaku Kekerasan Seksual dalam Perspektif Rehabilitasi Psikologis - Sayib Fauzi Adiansyah; Fanny Tanuwijaya; Yusuf Adiwibowo (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Children are a vulnerable group when children commit acts of sexual violence because of factors or causes such as environmental influences, past trauma, and post-incident trauma, so that with these influences and traumas children experience mental and psychological disorders, if not handled with an approach that can touch the child's mental and psychological, then it is likely that the child will be a recidivist. This study uses a normative juridical type with a statutory, conceptual, case, and comparative approach, legal materials are obtained from qualitative methods. The results of the study indicate that psychological rehabilitation is urgently applied because this approach is considered to be able to overcome mental and psychological disorders of children who commit sexual violence so that children recover from the disorders faced by children so that children do not become recidivists. Referring to the Netherlands and Sweden which implement psychological rehabilitation with high success rates. So the future regulations in Indonesia to handle children who commit sexual violence are to use a psychological rehabilitation approach, by adding provisions for psychological rehabilitation in additional criminal penalties contained in the SPPA Law or revising the TPKS Law to psychological rehabilitation.